Neural mechanisms linked to treatment outcomes and recovery in substance-related and addictive disorders - Mestre-Bach, Gemma; Potenza, Marc N (Dialogues in Clinical Neuroscience, 2024)
The present review focuses on potential neural mechanisms underlying recovery from psychiatric conditions characterised by impaired impulse control, specifically substance use disorders, gambling disorder, and internet gaming disorder. Existing treatments (both pharmacological and psychological) for these addictions may impact brain processes, and these have been evaluated in neuroimaging studies. Medication challenge and short-term intervention administration will be considered with respect to treatment utility. Main models of addiction (e.g., dual process, reward deficiency syndrome) will be considered in the context of extant data. Additionally, advanced analytic approaches (e.g., machine-learning approaches) will be considered with respect to guiding treatment development efforts. Thus, this narrative review aims to provide directions for treatment development for addictive disorders.
Keywords: neurobiology; recovery; substance-related disorders; gambling disorder; internet gaming disorder; impulsivity; addictive behaviours; internet addiction; JCR; Scopus